Role of AP-endonuclease (Ape1) active site residues in stabilization of the reactant enzyme-DNA complex - Batebi, Hossein; Dragelj, Jovan; Imhof, Petra (Proteins-Structure Function and Bioinformatics, 2018)
Apurinic/apyrimidinic endonuclease 1 (Ape1) is an important metal-dependent enzyme in the base excision repair mechanism, responsible for the backbone cleavage of abasic DNA through a phosphate hydrolysis reaction. Molecular dynamics simulations of Ape1 complexed to its substrate DNA performed for models containing 1 or 2 Mg2+-ions as cofactor located at different positions show a complex with 1 metal ion bound on the leaving group site of the scissile phosphate to be the most likely reaction-competent conformation. Active-site residue His309 is found to be protonated based on pKa calculations and the higher conformational stability of the Ape1-DNA substrate complex compared to scenarios with neutral His309. Simulations of the D210N mutant further support the prevalence of protonated His309 and strongly suggest Asp210 as the general base for proton acceptance by a nucleophilic water molecule.
Created from Fastlane, Scopus look-up
Keywords: abasic site; DNA repair; endonuclease; metal-ions; molecular dynamics; pKa values; protein-DNA complex